2019
DOI: 10.1002/brb3.1279
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stenting for idiopathic intracranial hypertension with venous sinus stenosis

Abstract: Objectives Idiopathic intracranial hypertension (IIH) is characterized by elevated intracranial pressure of unknown etiology and venous sinus stenting may be an optional treatment. We aimed to evaluate the effects of venous sinus stenting on visual function, intracranial pressure, and trans‐stenotic pressure gradient of the patients with IIH and to determine effects of baseline BMI or weight changes on subjective vision outcome and intracranial pressure. Methods From Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…While improvements were also noted in a portion of our patients for BCVA and mean deviation, a smaller percentage met preset criteria for meaningful improvement than in most prior studies. For example, the 2019 Liu et al study found 84.2% of patients reported significant improvement or recovery in their visual acuity (20). The difference is probably explained by baseline differences between the study population, as the baseline visual field mean deviation in the worse eye was −16.3 dB in the Liu et al study compared to a baseline visual field mean deviation of only −4.90 dB in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…While improvements were also noted in a portion of our patients for BCVA and mean deviation, a smaller percentage met preset criteria for meaningful improvement than in most prior studies. For example, the 2019 Liu et al study found 84.2% of patients reported significant improvement or recovery in their visual acuity (20). The difference is probably explained by baseline differences between the study population, as the baseline visual field mean deviation in the worse eye was −16.3 dB in the Liu et al study compared to a baseline visual field mean deviation of only −4.90 dB in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…The clinical outcomes of dural sinus stenting are related to headache, but especially improvement of visual parameters (visual acuity, papilledema), and as a secondary achievement, the improvement or disappearance of the tinnitus. In the published meta-analysis and retrospective reviews of case series ( Table 1 ), there was a consistent benefit with respect to these parameters: headache subsided or was significantly improved in 73–93% of patients, papilledema in 68–100%, visual acuity and visual field improvement in 70.3–86.5%, and tinnitus in 84.5–100% of patients [ 57 , 61 , 65 , 70 , 71 , 72 , 73 ].…”
Section: Management Of Iihmentioning
confidence: 90%
“…Quantitative assessment of visual field loss was possible for 82 patients (163 eyes) before and after stenting based on five studies that reported mean deviations. 34,38,46,52,62 Among these 163 eyes, the average mean deviation was À12.83 dB prior to stenting and improved to À7.53 dB poststenting.…”
Section: Visual Functionmentioning
confidence: 98%
“…Quantitative assessment of prestent ICP was reported in 461 patients (mean: 35.3 cm H 2 O) and poststent ICP was reported in 196 patients (mean: 19.5 cm H 2 O). 46,51 The difference between mean pre-and poststent ICP was 16 cm H 2 O, but this must be understood with the caveat that the sample sizes in the two groups differed. Data on long-term (>1-year poststent) opening pressure is scarce, since repeat LPs are generally performed only in patients who are not doing well clinically.…”
Section: Opening Pressurementioning
confidence: 99%